Reciprocity in Organisations - Evidence from the WERS - Florian Englmaier; Thomas Kolaska; Stephen G. Leider (Center for Economic Studies and ifo Institute (CESifo), 2015)
Recent laboratory evidence suggests that social preferences may affect contractual outcomes under moral hazard. In accordance with previous research, this paper uses written personality tests for job candidates as a proxy for whether firms care about personality traits of employees, in particular whether these employees are inclined towards reciprocity. Using the British Workplace Employment Relations Survey 2004 (WERS) we find that behavior of employers and employees is consistent with the presence of gift-exchange motives: firms that screen applicants for personality are more likely to pay generous wages and to provide (non-pecuniary) benefits like employer pension, on-the-job training, or job security. Firms likewise benefit from reciprocal employees as they can implement more team-working and are generally more successful. Other modern human resource practises like competency tests or incentive pay only poorly predict these patterns. Moreover, there is no association between dismissals and personality tests, indicating that personality tests do not merely improve the fit between applicant and employer. Hence, we conclude that motivation based on gift-exchange motives remains as the most plausible explanation for our results.
Keywords: D22; M52; 330; reciprocity; organisational structure; employee compensation